Nghiên cứu chế tạo vật liệu polyme phân hủy sinh học trên cơ sở nhựa polypropylen gia cường bằng sợi nứa. Phần 1. Ảnh hưởng của nồng độ dung dịch tới hiệu ứng tổng trở khổng lồ - Diệu và cộng sự, Trần Vĩnh (Vietnam Journal of Chemistry, 2014)
Neohouzeaua dullooa fibers were prepared by mechanical method. Its composition and morphology of fibers were studied. The analytical result shown that, most of hemicelluloses and lignin were removed. FTIR spectroscopy shows that strong sharp peak in the untreated bamboo spectrum at about 1736 cm-1 corresponding to carbonyl group (>C=O), but this peak disappeared in alkaline treated bamboo spectrum. Bamboo fiber reinforced polypropylene grafted maleic anhydride composites have been prepared by 50% fiber contents. The mechanical properties of composite were also tested.